2016
DOI: 10.1038/srep34666
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Braun Lipoprotein (BLP) exhibits endotoxemia – like pathology in Swiss albino mice

Abstract: The endotoxin lipopolysaccharide (LPS) promotes sepsis, but bacterial peptides also promote inflammation leading to sepsis. We found, intraperitoneal administration of live or heat inactivated E. coli JE5505 lacking the abundant outer membrane protein, Braun lipoprotein (BLP), was less toxic than E. coli DH5α possessing BLP in Swiss albino mice. Injection of BLP free of LPS purified from E. coli DH5α induced massive infiltration of leukocytes in lungs and liver. BLP activated human polymorphonuclear cells (PMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 82 publications
(105 reference statements)
1
18
1
Order By: Relevance
“…We previously observed that serum AGP-1 preferentially inhibits the TLR-4 agonist bacterial lipopolysaccharide (LPS), but not TLR-2 agonist Braun Lipoprotein (BLP) mediated inflammatory responses both in vivo and in vitro (24,25). We now show that the hepatocytederived serum AGP-1 (sAGP-1) is proinflammatory, while the neutrophil derived glycoforms (nAGP-1) primarily display antiinflammatory activity.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…We previously observed that serum AGP-1 preferentially inhibits the TLR-4 agonist bacterial lipopolysaccharide (LPS), but not TLR-2 agonist Braun Lipoprotein (BLP) mediated inflammatory responses both in vivo and in vitro (24,25). We now show that the hepatocytederived serum AGP-1 (sAGP-1) is proinflammatory, while the neutrophil derived glycoforms (nAGP-1) primarily display antiinflammatory activity.…”
Section: Introductionmentioning
confidence: 80%
“…The labelled neutrophils (1x10 6 cells/well) were incubated with sAGP-1 or nAGP-1 (25, 50 and 100 µg/ml) in triplicate wells in twelve well cell culture plates (Nest Biotechnology Co. Ltd., China) pre-coated with 0.2% gelatin. Unbound neutrophils were removed by washing twice with HBSS/A and the adherent neutrophils were visualized and photographed at a magnification of 10x by fluorescent microscopy (Motic BA410 fluorescence microscope, Hong Kong; with Nikon DS-Qi2 camera, Japan) (25). The number of cells adhered in each well was determined by counting the cells adhered in 10 randomly chosen fields using ImageJ software and then calculating the average number of cells adhered per field.…”
Section: Human Neutrophil Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various inflammation-associated factors, including LPS, TNF-α, IL-1, nitric monoxide, PAF, Braun’s lipoprotein (BLP), and high-mobility group box 1 protein, promote inflammation leading to sepsis ( 39 , 40 ). It has been reported that anti-TNF antibody protects mice from LPS-induced lethal shock in a dose-dependent manner ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total lipids were extracted by using the Bligh and Dyer method (38), dried under nitrogen, and then reconstituted in methanol. A methanolic aliquot was used to quantify acyl-PAF, alkyl-PAF (C16: predominantly hexadecyl at the sn-1 position of GPC), lyso-PC, and lyso-PAF as described previously (16,43,44). Products or substrates present at the end of the third minute during platelet aggregation were measured relative to C16:0-d 4 -PAF (Cayman Chemical, Ann Arbor, MI) and are expressed as the mean number of nanomoles per assay from two independent experiments.…”
Section: Lc-ms Analysis Of Phospholipids During Platelet Aggregationmentioning
confidence: 99%